This week in pre-calc, we learned how to solve a quadratic equation by factoring. The equation * + bx + c = 0. A, B, & C *are all constant terms and A cannot be equal to 0. When factoring a quadratic equation, you use the zero product property. This means you take your quadratic equation and you start by factoring. Once you’re done factoring, you’ll have 2 terms that should be equal to 0.

Ex. * -5x + 6 = 0*

(x – 2)(x-3) = 0

Once you factor your equation, you take each term and find out the value of x in order for the term to be equal to 0.

Ex. (x-2) = a (x-3) = b

a=0

b=0

a = (x-2) = 0, x = +2

b = (x-3)=0, x = +3

Basically you’re taking the opposite number to find x in order to make the term equal to 0.

(x – 2)(x-3) = 0

(2-2)(3-3) = 0

(0)(0)=0